Fuel properties, dry matter losses and combustion behavior of wood chips stored at aerobic and anaerobic conditions. (November 2020) - Kuptz, Daniel; Lesche, Simon; Mendel, Theresa; Mack, Robert; Rist, Elisabeth; Schön, Claudia; Hartmann, Hans
Abstract: Aerobic and anaerobic storage of wood chips from coniferous forest residues, coniferous energy roundwood and short rotation coppice were investigated regarding dry matter losses, energy losses and changes in fuel properties using several approaches, i.e. a field trial with 90 m 3 wood chip piles, small-scale storage containers (0.5 m 3 ) incl. greenhouse gas measurements and miniature bunker silos (1.5–2 m 3 ). After storage, selected fuels were combusted in a 30 kW wood chip boiler and emissions (CO, NOX, TPM) were measured. Dry matter losses in fleece-covered piles were 7%–9% after 153 days of storage. Drying compensated for energy losses. Container trials achieved full anaerobic conditions in the lab reducing dry matter losses to 0.4–2% while preserving fuel properties. Methane emissions during anaerobic storage in containers were low. Anaerobic conditions could not be achieved in outdoor bunker silos due to insufficient airtightness. The mass fraction of H2 O in fuels increased in bunker silos by 4.2–10.4% due to precipitation and dry matter losses up to 22% were recorded. During combustion, CO and TPM emissions were often increased significantly with materials that were stored in silos or piles compared to technically dried fuels, most likely due to changes in their woody or physical-mechanical structure and their mass fraction of H2 O. Anaerobic storage might in theory be an interesting option to reduce dry matter losses but could not sufficiently be realized during this study using miniature bunker silos. For many applications, aerobic storage in fleece-covered piles seems preferable to anaerobic storage. Highlights: Five months storage of wood chips in piles led to dry matter losses of up to 9%. Anaerobic storage prevented mass losses and changes in fuel properties on lab-scale. Methane emissions during anaerobic storage of wood chips were low. Application of anaerobic wood chip storage in small bunker silos was not successful. Combustion of wood chips from outdoor storage can lead to high CO and TPM emissions.